(untitled) (American Journal of Islam and Society, 2009)
This book endeavors to define a specific term for modern Arab art, which is most often considered a continuation of Islamic or ethnic art or a subordinate copy of western trends. This academic text, which targets audiences interested in contemporary art or the Arab world, or both, is divided into three parts: “Background and Definitions,” “Modern Arab Aesthetics,” and “The Arabic Letter in Art.” It contains forty images within the text and thirty-two plates of contemporary works of art by Arabs ...